2011
DOI: 10.1089/jmf.2010.1108
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects ofEmblica officinalisinl-Arginine-Induced Acute Pancreatitis in Rats

Abstract: Acute necrotizing pancreatitis is characterized by focal macroscopic or diffuse necrosis, hemorrhage, and vascular thrombosis of the pancreas. Current treatment options are limited to supportive and symptomatic interventions. A large amount of experimental work is ongoing to identify novel therapeutic agents for acute pancreatitis. The present study was carried out to explore the beneficial effects of Emblica officinalis, a medicinal plant of India, on acute pancreatitis. Ascorbic acid is one of the major chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Serum amylase and lipase are the biochemical tests used to diagnose acute pancreatitis (Sidhu et al 2011). Administration of L-arginine produced significantly higher levels of serum amylase at 24 h and day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Serum amylase and lipase are the biochemical tests used to diagnose acute pancreatitis (Sidhu et al 2011). Administration of L-arginine produced significantly higher levels of serum amylase at 24 h and day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Amla contains gallic acid which is a potent polyphenol and has been found to improve immunity (Singh et al 2011). It is also a rich source of pectin, an important form of dietary fiber that regulates the bowel action, is anti-diabetic, and treats scurvy and pulmonary tuberculosis (Ganju et al 2003;Yokozawa et al 2007;Sidhu et al 2011). Because of its excellent therapeutic values, it is extensively used in Ayurvedic medicines like Chyavanprash, Triphalahurna, Brahmi rasayan and Madhumehga (Anon 2003).…”
Section: Introductionmentioning
confidence: 99%
“…FACS assays confirmed that 97.58% of the isolated cells expressed CD29 (Figure 3A), 0.69% expressed CD34 (a myeloid progenitor cell antigen also presented in endothelial cells and some fibroblasts, Figure 3B); 66.88% expressed CD44 (a stem cell marker, Figure 3C), 2.24% expressed CD45 (a hematopoietic and leukocyte marker, Figure 3D) [21]; and 63.80% of the cells expressed CD90 (Figure 3E). Thus, the cells showed the antigenic profile of BMMSCs [22].…”
Section: Resultsmentioning
confidence: 95%